Protein Repair and Degradation during Aging - Bertrand Friguet (The Scientific World Journal)
Cellular aging is characterized by a build-up of oxidatively modified proteins. The steady-state level of oxidized proteins depends on the balance between the rate of protein oxidative damage and the rates of protein degradation and repair. Therefore, the accumulation of oxidized protein with age can be due to increased protein damage, decreased oxidized protein degradation and repair, or the combination of both mechanisms. The proteasomal system is the major intracellular proteolytic pathway implicated in the degradation of oxidized protein, and the peptide methionine sulfoxide reductase catalyzes the reduction of methionine sulfoxide (i.e., oxidized methionine) to methionine within proteins. A short summary on protein oxidative damage and oxidized protein degradation is given, and evidence for a decline of proteasome function with age is presented. Arguments for the implication of peptide methionine sulfoxide reductase in the age-related accumulation of oxidized protein are also discussed.